Type 2M vWD Resulting from a Lysine Deletion within a Four Lysine Residue Repeat in the A1 Loop of von Willebrand Factor - Hilbert, L.; Jenkins, P. V.; Gaucher, C.; Meriane, E.; Collins, P. W.; Pasi, K. J.; Mazurier, C. (Thrombosis and Haemostasis, 2000)
Type 1 von Willebrand disease is characterized by a decreased plasma concentration of functionally normal von Willebrand factor (vWF) whereas type 2M is characterised by an abnormal vWF displaying decreased affinity for platelets. In these two types of patients, the multimeric structure of vWF is normal.We report here the identification, in two unrelated families from the UK and Algeria, of an in-frame 3 bp deletion, at the heterozygous state, resulting in the deletion of a lysine residue within a four lysine repeat at position 642-645 of the mature vWF subunit (del K1405-1408 in prepro vWF). The patients who have a discrepancy between vWF antigen level and vWF ristocetin cofactor activity exhibited decreased ristocetin-induced binding but only a slight decrease in the percentage of high molecular weight (HMW) multimers in plasma.Recombinant vWF harbouring this deletion did not bind to platelet GPIb in the presence of ristocetin or botrocetin although the protein is multimerized. Consequently, this lysine deletion was considered as a type 2M vWD mutation.
Keywords: von Willebrand factor; von Willebrand disease; mutation; recombinant vWF; Cos-7 cells